EXPERIENCE IN DESIGN OF LED LAMPS - and; and (Municipal economy of cities. Series: «Economy science», 2013)
On the basis of the standard of local lighting fixture designed LED light to illuminate the work place near the PC. Experiments were performed to study the light distribution lamp constructed.